2014
DOI: 10.2174/1570162x1201140716101512
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection, Antiretroviral Therapy Initiation and Longitudinal Changes in Biomarkers of Organ Function

Abstract: Background HIV is associated with end-organ diseases of aging via unclear mechanisms. Longitudinally assessing how HIV infection and ART initiation affect biomarkers of end organ function/disease could clarify these mechanisms. We investigated longitudinal changes in clinical biomarkers following 1) HIV infection and 2) ART initiation with evidence of viral suppression. Methods Cohort: Veterans Aging Cohort Study Virtual Cohort (VACS VC). VACS VC is a longitudinal cohort of HIV infected (HIV+) and race-ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…This reduction in ALT level in the control group was about 25%. Similar findings were also documented in few studies done in different parts of the world, 12,13,14,15 and contradictory findings were also documented in various studies from different parts of the globe. 4,5,6,7,8,16,17 Among the HCV positive HIV patients at the time of initiation of ART and at 6 months after initiation of ART, approximately 84% of the patients having CD4 count less than 200/cu.mm had improved and crossed CD4 count above 200/cu.mm, which shows a remarkable improvement, these findings were supported by various studies done in different parts of the world.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This reduction in ALT level in the control group was about 25%. Similar findings were also documented in few studies done in different parts of the world, 12,13,14,15 and contradictory findings were also documented in various studies from different parts of the globe. 4,5,6,7,8,16,17 Among the HCV positive HIV patients at the time of initiation of ART and at 6 months after initiation of ART, approximately 84% of the patients having CD4 count less than 200/cu.mm had improved and crossed CD4 count above 200/cu.mm, which shows a remarkable improvement, these findings were supported by various studies done in different parts of the world.…”
Section: Discussionsupporting
confidence: 84%
“…4,5,6,7,8,16,17 Among the HCV positive HIV patients at the time of initiation of ART and at 6 months after initiation of ART, approximately 84% of the patients having CD4 count less than 200/cu.mm had improved and crossed CD4 count above 200/cu.mm, which shows a remarkable improvement, these findings were supported by various studies done in different parts of the world. 12,13,14,15 And among the HCV negative HIV positive patients, the improvement in CD4 counts after 6 months of initiation of ART were marked by about 90% of the patients crossing CD4 count above 200/cu.mm from pre-ART CD4 count below 200/cu.mm, similar finding is universal and is the basis for ART. 18 …”
Section: Discussionmentioning
confidence: 72%
“…An increasing number of chronic disease complications, such as HIV-associated neurocognitive disorders (HAND), are therefore the focus of current efforts to improve quality of life for HIV-infected (HIV+) individuals. HAND remains disturbingly common despite ART, for reasons that are only partially understood, occurring in 30–60% of unselected HIV+ persons, even when the virus is undetectable [5, 6]. Intensive research has suggested many possible mechanisms and etiologies for HAND, including persistent low-level immune activation and inflammation within the central nervous system (CNS) [4, 7, 8], comorbid conditions [9], and accelerated aging [10], but few of these mechanisms are directly actionable, and effective interventions remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In both ART‑naïve chronic HIV infection (CHI) adult and children patients, low HDL-C was the most frequently observed abnormality and there existed a significant relationship between lipid parameters and viral load [10, 11]. Results from the Veterans Aging Cohort Study showed that HIV infection was associated with decreased TC, HDL-C, LDL-C and elevation of TG, ART initiation did not reverse alteration in TG or LDL-C to pre-HIV infection levels [12]. This suggests that HIV infection may influence lipids regardless of ART status.…”
Section: Introductionmentioning
confidence: 99%